THE EFFECTIVENESS OF SPLINTING SKILLS EDUCATION IN CLOSED FRACTURE CASES USING THE SEMINAR AND SELF DIRECT VIDEO METHODS ON THE KNOWLEDGE LEVEL OF GRADE 12 STUDENTS OF SMAN 4 JAKARTA - Rizky Rizaldi; Bahreni Yusuf; Hendik Wicaksono (JOURNAL EDUCATIONAL OF NURSING(JEN), 2026)
Background: Fractures resulting from traffic accidents are injuries that have the potential to cause disability if not treated appropriately. One technique used is splinting to prevent bone displacement, reduce pain, and protect surrounding tissue. Students' knowledge of splinting techniques is still low, requiring effective educational methods, such as seminars and self-directed videos. Objective: To determine the effectiveness of splinting skills education for closed fractures using seminars and self-directed videos on the knowledge level of 12th-grade students at SMAN 4 Jakarta. Methods: This study used a Quasi-Experimental design with a Pretest-Posttest with Control Group Design. 144 students were selected using simple random sampling and divided into an intervention group (self-directed video) and a control group (seminar), each with 72 respondents. The research instrument consisted of pretest and posttest questionnaires. Data analysis used the Wilcoxon Signed Rank Test. Results: There was an increase in knowledge in both groups with a p-value <0.05, where the posttest score was higher than the pretest. The positive rank score for the intervention group was 61 and for the control group, 55. Conclusion: Education on splinting skills for closed fractures using seminars and self-directed video was equally effective in improving the knowledge of 12th-grade students at SMAN 4 Jakarta. However, the self-directed video method yielded higher improvement than the seminar method, thus concluding that the self-directed video method is more effective in improving student knowledge.